IMPLIKASI NETTIQUETTE SEBAGAI ADAB BERMEDIA SOSIAL DALAM DAKWAH RELIGI - NOVI ANDAYANI PRAPTININGSIH; AMI KUSUMA HANDAYANI (Universitas Muhammadiyah Prof Dr Hamka, 2017)
Dakwah through social media must have Nettiquette (Netiket), which stands for internet etiquette or internet ethics that governs social media in social world. Social media as a medium of religious dakwah, can serve as: Educator (Muaddib), Information Straighteners (Musaddid), Pembaharu (Mujaddid), Unifier (Muwahid), and Warriors (Mujahid). With dakwah, able to encourage the enforcement of Islamic values, enliven syiar Islam, and promote a positive image of Islam and rahmatan lil'alamin. The need for online dakwah revitalization in facing the dakwah challenge for information society. Revitalizing dakwah is a process of re-enforcing dakwah steps both quantity and quality in all aspects of life towards the realization of an Islamic life. Increasing the intensity (quantity) and the quality of da'wah is higher and advanced, it is expected that dakwah really have a direct effect in shaping the life of an Islamic society. Keywords : Implications, Nettiquette, well-mannered, Social Media, Religious Dakwah